Ethnobotany of cassava (Manihot esculenta Crantz) in the traditional peri-urban Sundanese community of Cireundeu Hamlet, Cimahi City, West Java, Indonesia - BUDI IRAWAN; KARINA MAHESWARI SAFIRA; ANNISA ANNISA; ENENG NUNUZ ROHMATULLAYALY; MUHAMMAD IHSAN; SURYANA SURYANA; JOHAN ISKANDAR; BUDIAWATI S. ISKANDAR (Society for Indonesian Biodiversity, 2024)
Abstract. Irawan B, Safira KM, Annisa, Rohmatullayaly EN, Ihsan M, Suryana, Iskandar J, Iskandar BS. 2024. Ethnobotany of cassava (Manihot esculenta) in the traditional peri-urban Sundanese community of Cireundeu Hamlet, Cimahi City, West Java, Indonesia. Biodiversitas 25: 116-128. The community of Cireundeu Hamlet is one of the Sundanese traditional communities that still maintain wisdom in processing and using cassava (Manihot esculenta Crantz) as staple food (rasi) and foodstuff. Many landraces of cassava have the potential to develop into superior varieties, and research is necessary to make cassava a year-round food. The aim of this study is to elucidate the ethnobotanical knowledge of the rural Sundanese community on cassava, namely on various landraces and their folk classification, traditional farming management, and uses. Based on a case study of the traditional people in a peri-urban area of Cireundeu Hamlet, Cimahi City, West Java, Indonesia, mixed methods, i.e., qualitative and quantitative, were used in this study. There are seven landraces of cassava used as foodstuff that are traditionally managed by the Cireundeu people, including sampeu apuy, sampeu bodas, sampeu gambir lembang, sampeu garnawis, sampeu hideung, sampeu karihkil, and sampeu mentega. Based on Relative Frequency of Citation, the highest values are sampeu bodas (0.96) and sampeu garnawis (0.93). These cassava landraces can be distinguished by the Cireundeu people based on characteristics of petiole color, stem color, apical leaf color, leaf color, and taste of the tubers. Based on folk taxonomy, cassava is classified into five levels: level 0 (unique beginner), known as tutuwuhan and pepelakan (plants); level 1 (Life form) known as beubeutian (tubers); level 2 (generic) known as sampeu karet and sampeu, a genus from Manihot esculenta; level 3 (species) known as sampeu (sweet-cassava, Manihot esculenta Crantz) and sampeu karet (bitter cassava, M. carthagenensis subsp. glaziovii); and level 4 (specific). The processing and use of cassava are carried out both in traditional and modern ways, including using apical leaves as lalab or boiled vegetables and using the roots as the basic ingredients for making rasi (sangueun), tapioca flour, and snacks.